An aroD Ochre Mutation Results in a Staphylococcus aureus Small Colony Variant That Can Undergo Phenotypic Switching via Two Alternative Mechanisms - Zhang, Ping; Wright, John A.; Osman, Ahmed A.; Nair, Sean P. (Frontiers in Microbiology, 2017)
Staphylococcus aureus can undergo phenotypic switching between a normal colony phenotype (NCP) and a small colony variant (SCV). The SCV phenotype confers increased antibiotic resistance and the capacity to persist within human tissues and cells, and because these cells can revert back to the NCP they cause chronic and/or recurrent infections that are very difficult to treat. A complete picture of the genetic events that can lead to phenotypic switching in S. aureus is currently lacking. We describe the selection of an SCV with a previously unreported genetic alteration leading to an ochre mutation of aroD. In addition to the known mechanisms of phenotypic switching between the SCV and the NCP we describe a previously unreported mechanism involving tRNA ochre suppressors arising. The ochre suppressor strains had wild type growth rates and restored antibiotic sensitivity, similar to the wild type strain. However, whilst they had increased virulence compared to the SCV parent strain, their virulence was not restored to that of the NCP parental strain. These findings establish that phenotypic switching between the NCP and SCV states can give rise to strains with different pathogenic potential.